The economics of investment in high speed rail: Summary and conclusions - John Preston (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
From its origin with the Tokaido Shinkansen in 1964, High Speed Rail (HSR), defined here as new rail lines capable of operating speeds of 250 kilometres per hour or more, has grown relatively slowly over the last 50 years, with the World HSR network as of late 2013 standing at under 22 000 km. However, the network has been growing rapidly in recent years. With the first opening as recently as 2007, China has already an HSR network of almost 10,000 km. with a further 9 000 km under construction (out of a worldwide total of 14,000 km of line under construction). Given the backdrop of an HSR investment boom, a roundtable was held in New Delhi in November 2013 with aim of achieving a better understanding of the economics of HSR given the evidence that is emerging from both well established (e.g. France and Japan) and from new HSR (e.g. China) schemes.
Keywords: 330